Mutualitas Si Tou Timou Tumou Tou: Hospitalitas Kultural Toleransi Komunitas Jawa Muslim dan Minahasa Kristen di Tondano - Rivo Wakulu (Journal of Education, Humaniora and Social Sciences (JEHSS), 2021)
This paper will analyze and provide a general description of the philosophical meaning of Si Tou Timou Tumou Tou in the Javanese Muslim and Christian Minahasa communities in Tondano. More deeply, the author tries to see how the philosophy of life of Si Tou Timou Tumou Tou, which is the slogan of the Minahasa people, is applied and lived by the Javanese Muslim and Christian Minahasa communities in Tondano as an glue and an effort to build relationships with the lives of various communities. This paper draws a temporary conclusion that in order to encourage peaceful relations and the creation of the maintenance of shared life, a concept of cultural hospitality that goes beyond tolerance is needed in accordance with the context of the problems in each region. Using a sociological perspective, this paper examines the extent to which cultural hospitality values can play a role in interfaith relations in Tondano. In the final section, this paper will explore the cultural concept of the Tondano people as embodied in the philosophy of life of Si Tou Timou Tumou Tou as an effort to go beyond tolerance between religious communities, while at the same time maintaining the existence of the historical heritage of local culture.